The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.2460/javma.2000.217.1025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of butorphanol and carprofen on the minimal alveolar concentration of isoflurane in dogs

Abstract: Results suggest that administration of butorphanol alone or in combination with carprofen significantly reduces the MAC of isoflurane in dogs; however, the effects of butorphanol and carprofen are additive, not synergistic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
57
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 16 publications
7
57
1
1
Order By: Relevance
“…In the present study, however, the administration of carprofen or meloxicam in combination with butorphanol provided only additive sevoflurane-sparing effects in dogs. Similar results have been observed in dogs after administration of butorphanol in combination with carprofen [16] and rabbits after administration of butorphanol in combination with meloxicam [30]. There is conflicting information in the literature regarding the effect of butorphanol on the MAC of inhalant anesthetics in dogs [16,25,27].…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…In the present study, however, the administration of carprofen or meloxicam in combination with butorphanol provided only additive sevoflurane-sparing effects in dogs. Similar results have been observed in dogs after administration of butorphanol in combination with carprofen [16] and rabbits after administration of butorphanol in combination with meloxicam [30]. There is conflicting information in the literature regarding the effect of butorphanol on the MAC of inhalant anesthetics in dogs [16,25,27].…”
Section: Discussionsupporting
confidence: 62%
“…Alibhai and Clarke [1] reported that carprofen minimally influenced the MAC of halothane in dogs. On the other hand, Ko et al [16] reported that preoperative oral administration of carprofen alone produced 6.24 ± 3.42% of the percentage MAC reduction, but the isoflurane-MAC values were not significantly different from control (0.90 ± 0.21% vs 1.03 ± 0.22%, P=0.069). In the present study, the preoperative subcutaneous administration of carprofen or meloxicam alone produced 11.3 ± 8.3% or 12.9 ± 10.2% reduction of the percentage MAC, respectively, that were significantly different compared to control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations